2009
DOI: 10.1016/j.brainres.2009.09.066
|View full text |Cite
|
Sign up to set email alerts
|

Role of adenosine A1 receptor in the perifornical–lateral hypothalamic area in sleep–wake regulation in rats

Abstract: The perifornical-lateral hypothalamic area (PF-LHA) has been implicated in the regulation of arousal. The PF-LHA contains wake-active neurons that are quiescent during nonREM sleep and in the case of neurons expressing the peptide hypocretin (HCRT), quiescent during both nonREM and REM sleep. Adenosine is an endogenous sleep factor and recent evidence suggests that adenosine via A 1 receptors may act on PF-LHA neurons to promote sleep. We examined the effects of bilateral activation as well as blockade of A 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 52 publications
3
25
0
Order By: Relevance
“…1A) [22] , consistent with previous reports [17] . Based on the location of microinjection sites, the areas of perfused drugs were confirmed to include the orexin neurons in the lateral hypothalamus.…”
Section: Identifi Cation Of the Site Of Drug Deliverysupporting
confidence: 83%
See 2 more Smart Citations
“…1A) [22] , consistent with previous reports [17] . Based on the location of microinjection sites, the areas of perfused drugs were confirmed to include the orexin neurons in the lateral hypothalamus.…”
Section: Identifi Cation Of the Site Of Drug Deliverysupporting
confidence: 83%
“…In addition to the key role in promoting wakefulness, abundant evidence has demonstrated that orexin neurons are a potential target in the sleep-producing effect of endogenous adenosine, in which blockade of adenosine A1 receptors in the lateral hypothalamus induces a signifi cant increase in wakefulness with a concomitant reduction in sleep [17,19] . Consistently, we found that the exogenous application of adenosine into the lateral hypothalamus enhanced sleep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CPA significantly suppressed the sleep-wake discharge activity of PF-LHA neurons. Doses of CPA (50μM) and CPDX (50μM) that suppressed and induced arousal, respectively, in our earlier study (Alam et al, 2009), significantly suppressed and increased Fos-IR in HCRT and non-HCRT neurons. These findings suggest that wake-promoting PF-LHA system is subject to increased endogenous adenosinergic inhibition and that adenosine acting via A 1 receptors, in part, inhibits HCRT neurons to promote sleep.…”
mentioning
confidence: 51%
“…Adenosine and A 1 R agonists inhibit activity of the hypocretin/orexin neurons in this area via A 1 R which promotes sleep [67,68]. On the other hand, blockade of A 1 R in such neurons causes a pronounced increase in wakefulness [68,69]. Adenosine reduces the frequency of action potentials in hypocretin/orexin neurons by depressing excitatory synaptic transmission to these cells.…”
Section: Sleep-wake Regulationmentioning
confidence: 99%